Pola dan Komposisi Pengeluaran Wisatawan Domestik di Kabupaten Bantul - Rizky Amalya; Vertue Volcano; Cahya Danu Rahman; Ervina (Jurnal Riset Daerah, 2026)
Tourism has become an important driver of regional economic development, particularly in destinations with high domestic visitor flows such as Bantul Regency. This study aims to analyze the spending patterns and expenditure composition of tourists visiting tourism destinations in Bantul and to identify policy implications for increasing the local economic impact of tourism activities. The research applies a quantitative descriptive approach using primary data collected through survey questionnaires distributed to tourists aged 17 years and above who have visited tourism destinations in Bantul Regency. The data were analyzed using descriptive statistical techniques to examine the distribution and proportion of tourist expenditures across several spending categories. The results of the survey, which was completed by 75 respondents, show that the average tourist expenditure per visit is IDR 133,526.62, with the largest share allocated to food and beverages (30.90 percent) and transportation (26.86 percent), followed by souvenirs (14.21 percent) and accommodation (11.25 percent). Spending on tourism attractions and entertainment remains relatively low, indicating limited diversification of tourism expenditure. These findings suggest that tourism in Bantul is still characterized by short-duration visits focusing on basic travel needs. Strengthening experiential tourism, village-based tourism, and nature-based attractions could increase tourist expenditure and length of stay.